Sex‐related differences in left ventricular diastolic function and arterial elastance during admission in patients with heart failure with preserved ejection fraction: The PURSUIT HFpEF study. Issue 12 (22nd November 2018) - Hoshida, Shiro; Watanabe, Tetsuya; Shinoda, Yukinori; Ikeoka, Kuniyasu; Minamisaka, Tomoko; Fukuoka, Hidetada; Inui, Hirooki; Ueno, Keisuke; Suna, Shinichiro; Nakatani, Daisaku; Hikoso, Shungo; Yamada, Takahisa; et al.
Abstract : Background: We previously reported that an index of afterload‐related left ventricular diastolic function, operant diastolic elastance (Ed)/effective arterial elastance (Ea) = E/e'/(0.9 × systolic blood pressure), was significantly higher in elderly hypertensive women. We aimed to determine sex‐related differences in the E/e'‐related indices for left ventricular diastolic function and their related factors during admission in patients with heart failure with preserved ejection fraction (HFpEF). Hypothesis: Elderly HFpEF women exhibit severe left ventricular diastolic dysfunction associated with different left atrioventricular volume ratio. Methods: We divided 267 patients with HFpEF (men/women, 116/151) into two groups by age (≥75 years, n = 212; <75 years, n = 55). We examined the alterations of E/e', E/e'/stroke volume index = Ed, and Ed/Ea, and cardiac structure during admission. Results: Ed and Ea were significantly higher in women than in men, at admission, especially in patients ≥75 years. Before discharge, not only Ed and Ea but also Ed/Ea was significantly higher in women than in men, especially in patients ≥75 years. Elderly female patients had larger left atrial than left ventricular volume. Conclusions: Higher afterload‐related left ventricular diastolic elastance, Ed/Ea, in association with higher arterial elastance, Ea, accompanied by left atrioventricular volume mismatch was observed in elderly HFpEF women.